IMPELEMENTASI PEMBELAJARAN FIKIH IBADAH PADA SISWA KELAS VII MTS TANBIHUL GEHOFILIN BAWANG BANJARNEGARA - Nur Soimah; Naufal , Naufal (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2022)
The title of the implementation of religious jurisprudence learning in 7th grade students of MTs Tanbihul Ghofilin Bawang Banjarnegara, in this study having an educational background is one of the most important things for human life, which aims to make a good and good generation of course, but in every educational process especially in learning has an obstacle and obstacle, which occurs in learning at MTs Tanbihul Ghofilin especially grade 7, this research has a purpose. 1) to find out the efforts and learning strategies, 2) learning methods. 3) learning factors, using quantitative methods that produce descriptive data, with data collection techniques through interview observations and documentation, in analyzing data systematically and then organizing the data, describing the data into units and compiling into a pattern that produces a conclusion, in learning What happened at MTS Tanbihul Ghofilin was in accordance with the objectives and procedures for learning, then in each lesson several factors were found, both supporting and inhibiting factors that came from internal and external sources, and various efforts that had been made by the teacher in charge of the 7th grade fiqh subject at MTs Tanbihul Ghofilin Onion Banjarnegara. Keywords : ,